Purification of Industrial Waste Water by Electrocoagulation - I, Mavlanova Yu.; A, Sabirova D.; B, Artikboyev X. (European Journal of Life Safety and Stability (2660-9630), 2022)
The article presents purification of industrial wastewater by electrocoagulation is based on electrolysis using metal (steel or aluminum) anodes subjected to electrolytic dissolution under the influence of an electric field. The electrocoagulation method is technologically quite simple and effective - it is used to remove inorganic and organic contaminants from wastewater - heavy metals, chromates, phosphates, finely dispersed impurities, emulsified oils, fats and oils and petroleum products, organic suspensions, etc.